Interaksi Power dan Knowledge dalam Konstruksi Mazhab Fiqih dalam Perspektif Historis - Rusli Rusli (Islamica: Jurnal Studi Keislaman, 2009)
This paper deals with the development of the term madhhab in the history of Islamic law. As a vital concept in Islamic law, the meaning of madhhab has undergone several changes. At first, it was related only to a personal opinion of a mujtahid. Then it was related to a view of ulama belonging to a particular school of thought, and finally it is understood as a doctrinal opinion with distinctive legal concepts and methodologies controlled by the authority of the ulama who occupy the axis of the madhhab hierarchy. Some madhhabs have gone extinct due to their irrelevant concepts, but some others managed to survive due to their ability to make a ?great synthesis? between reason and revelation, text and context. Some of these surviving madhhabs have even become the official madhhab of a Muslim state and made obvious contribution in the formation of Islamic law in that particular country. It is to this issue that this paper is mainly concerned with.